Socialization Disrupted: The Intergenerational Transmission of Political Engagement in Immigrant Families - Magda Borkowska; Renee Luthra (International Migration Review, 2022)
In this article, we examine the political socialization process in immigrant families based on the UK Household Longitudinal Study (UKHLS). We find that international migration disrupts the intergenerational transmission of political engagement: associations between voting, political interest, and parent and child socioeconomic status are weaker in immigrant families than in families without a migration background. In particular, the voting behavior of immigrants and their children in particular is only partially explained by standard models of political socialization. In contrast, characteristics specific to the international migration process, including sending country experiences, characteristics of the migration journey, and the pathway to citizenship are critical determinants of voting for immigrant parents, and through political socialization, for their UK-raised children.
Keywords: 320; second generation; political participation; intergenerational transmission